Cost estimation of ready-to-serve composite milk-sorghum based breakfast smoothie - Rani, Rekha; Sabikhi, Latha; MH, Sathish Kumar (Indian Journal of Dairy Science, 2018)
Abstract In the present investigation, smoothie (a ready-to-drink nutritious breakfast option) was prepared using cow milk, germinated sorghum flour, mango pulp, carrot juice and sugar without addition of any colour. The product was rich in vitamin A, calcium and iron and dietary fibre. Production cost of the product was calculated using certain basic assumptions such as production in an existing plant under operation that was operated in one 8 h shift per day for 300 days a year with handling capacity would be 1000 kg per day. Various heads such as cost of raw material, manpower, power and utilities, equipment and machineries, fixed cost (interest on total fixed capital, investment and working investment), marketing and distribution cost (after adding 20% on production cost) were included in it. The selling cost of sorghum based breakfast smoothie was Rs. 94.36/kg and for Rs. 18.87 for a single serving of 200 g.